Odpowiedzi

2010-03-28T11:07:05+02:00
A) -3x=2x-10
-3x-2x=-10
-5x=-10
x=2
b) 2x-2=7-x
2x+x=7+2
3x=9
x=3
c) 10=4-2x
2x=4-10
2x=-6
x=-3
d) -(2x-1)=4
-2x+1=4
-2x=4-1
x=-3/2
e) 2(x+1)=x
2x+2=x
2x-x=-2
x=-2
f) 2t-(3t+1)=6
2t-3t-1=6
-t=6+1
t=-7
g) -(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
h) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y-2y=18-18
0=0
i) (x-7)-2(3x+5)=3
x-7-6x-10=3
-5x=3+17
x=-4
5 3 5
2010-03-28T11:12:19+02:00
A) -3x=2x-10=-3x-2x=-10
=5x=-10/5
=x=-2
b) 2x-2=7-x=2x+x=7+2
3x=9/3
x=3
c) 10=4-2x=10-4=2x
2x=6/2
x=3
d) -(2x-1)=4=2x+1=4
2x=4-1/2x
x=2/3
e) 2(x+1)=x=2x+2=x
x=2
f) 2t-(3t+1)=6 = 2t - 3t-1=6 t=6+1
g) -(4+x)=2(3-x)= 4-x= 6-2x
-x+2x=6-4
x=2
h) 3(y+6)-y=2(y+9)=3y+18-y=2y+18
3y-y-2y=18-18
o=o-sprzeczne
i) (x-7)-2(3x+5)=3 x-7-6x+10=3
x=7+10
x=-4

2 4 2
2010-03-28T11:35:21+02:00
A)-3x=2x-10 b)2x-2=7-x c)10=4-2x
-3x-2x=-10 2x+x=7+2 2x=4-10
-5x=-10/: -5 3x=8/: 3 2x=-6/: 2
x=-2 x=3/8 ( w ułamku ) x=-3

d)-(2x-1)=4 e)2(x+1)=x f)2t-(3t+1)=6
-2x+1=4 2x+2=x 2t-3t+1=6
-2x=4-1 2x-x=2 -1t=6-1
-2x=3/:-2 x=2 -1t=5/:-1
x=-2/3 (w ułamku) t=-5

g) -(4+x)=2(3-x) h)3(y+6)-y=2(y+9) i)(x-7)-2(3x+5)=3
-4-x=6-2x 3y+18-y=2y+18 x-7-6x-10=3
-x-2x=4+6 3y-y-2y=18-18 x-6x=3+7+10
-3x=10/: -3 x=0 -5x=13/: -5
x=-0,3 x=-5/13 (w ułamku)
2 2 2